Urban expansion, economic development, and carbon emissions: Trends, patterns, and decoupling in mainland China’s provincial capitals (1985–2020) - Jiahui Zhao; Wei Chen; Zixuan Liu; Wei Liu; Keyan Li; Bei Zhang; Yonggen Zhang; Le Yu; Tetsuro Sakai (Ecological Indicators)
In 2020, the Chinese government set the objective of achieving carbon neutrality, making it essential to understand the urbanization process in order to effectively implement future sustainable development strategies. Here, we demonstrate the urbanization development of 31 provincial capitals in mainland China from 1985 to 2020, including changes in impervious surfaces, socio-economic development, carbon emissions, and population. Using elasticity coefficients and the carbon emissions causal equation for quantitative analysis, we explore the relationships among these factors. We found that the national urban expansion rate experienced rapid growth, followed by a slowdown, with the peak occurring between 2000 and 2005. In just 40 years, total urban area expanded from 11,280 km2 to 40,429 km2, with eastern cities growing faster than those in the west. Despite similar trends, different cities displayed four distinct spatial characteristics, shaped by factors such as topography, transportation, and policies. Moreover, urban economic development is gradually decoupling from carbon emissions, accompanied by a declining reliance on urban area expansion and a reduced growth rate of carbon emissions. A strong decoupling trend between economic growth and carbon emissions has already emerged in the South & Central and Northwest regions, offering a preliminary explanation for the observed slowdown in carbon emissions. The study provides a comprehensive overview of the urbanization process in mainland China, highlighting low-carbon urban transformations and revealing how government policies have significantly shaped the development patterns of Chinese cities. These findings offer valuable insights for policymakers to further promote sustainable development goals.